Nutritional and in vitro antioxidant properties of edible wild greens in Iberian Peninsula traditional diet - Martins, Dafne (2011)
Wild greens are nutritionally well-balanced vegetables. Herein, nutritional and in vitro antioxidant properties of the sprouts of three commonly used species were determined. Wild asparagus revealed the highest levels of moisture (84.6 g/100 g fw), ash (12.3 g/100 g dw), proteins (22.4 g/100 g dw), total sugars (9.24 g/100 g dw), including sucrose (4.27 g/100 g dw) and of the essential n-6 fatty acid linoleic acid (44.5 %); white bryony gave the highest contents of reducing sugars, including glucose (2.97 g/100 g dw), essential n-3 fatty acid α-linolenic acid (70.3 %), and the best ratios of PUFA/SFA and n-6/n-3 fatty acids (3.59 and 0.0907, respectively); black bryony showed the highest concentrations of carbohydrates (69.3 g/100 g dw), fructose and trehalose (3.83 and 1.34 g/100 g dw, respectively). Besides their culinary characteristics, their high content in vitamins (asparagus, 135 and 142 mg/100 g dw of total tocopherols and ascorbic acid respectively), chlorophylls (white bryony, 50.9 mg/100 g dw), carotenoids (23.3 mg/100 g dw) and phenolics (black bryony, 759 mg GAE/g extract), together with the antioxidant properties (EC50 values lower than 640 μg/ml) and potential health benefits increase their importance in traditional as well as in contemporary diets.